Computational Linguistics in the Netherlands 2001 2002
DOI: 10.1163/9789004334038_011
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Generation of Self-corrections Using Underspecification

Abstract: The focus of the present paper is on the interface between the first two components of a language production model, i.e. conceptualiser and formulator. We propose a method of how the incremental input for the formulator can be represented within an underspecification formalism. The proposed method can be used in dynamically changing environments, e.g. an airport supervision and information system, to produce descriptions of ongoing events. Because such a highly dynamic setting requires a real time production, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…For instance, Skantze and Hjalmarsson (2010) showed that an incremental generator using filled pauses and self-corrections achieved (in a wizard of Oz experiment) shorter response times and was perceived as more efficient than a non-incremental generator. Guhe and Schilder (2002) have also used incremental generation for self-corrections.…”
Section: Related Workmentioning
confidence: 99%
“…For instance, Skantze and Hjalmarsson (2010) showed that an incremental generator using filled pauses and self-corrections achieved (in a wizard of Oz experiment) shorter response times and was perceived as more efficient than a non-incremental generator. Guhe and Schilder (2002) have also used incremental generation for self-corrections.…”
Section: Related Workmentioning
confidence: 99%
“…24. Other discourse refOs are used in Guhe and Schilder (2002a), where they represent correction terms. These in turn are similar to discourse refOs establishing coordination relations in the generation of VP ellipses, simply called list in Guhe and Schilder (2002b).…”
Section: Notesmentioning
confidence: 99%